ANALISIS STRATEGI MARKETING LAYANAN PAYROLL (Studi Kasus Bank BNI Syariah KCP Jababeka-Cikarang) - Ardianto, Riski; Achmad, L.I; Kurniawati, Ria (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
In recent years, Islamic banking has experienced positive developments. With a situation like this, conventional banking will face new competition with the presence of Islamic banks. The competition is in its products, one of which is a payroll service product that can help a companies or institutes pay its employees en masse and efficiently at one time. At this time not only conventional banks have payroll service products, Islamic banks also have payroll service products that can meet the needs of companies or institutes in managing finances whose operating processes are adjusted to Islamic sharia principles. This study aims to determine the marketing strategies implemented in BNI Syariah, know the concept of the system of marketing payroll service product in BNI Syariah KCP Jababeka-Cikarang and find out obstacles faced by BNI Syariah in implementing the marketing the market strategy of its products. This study uses a qualitative approach, namely field research and library research. Field research, namely data collection techniques with the method of observation, interviews and documentation with marketing staff and customers of BNI Syariah KCP Jababeka-Cikarang so as to get accurate data in the research process. And library research, namely data collection techniques using written sources. Through interviews and observation it can be seen that the marketing strategy carried out by BNI Syariah KCP Jababeka-Cikarang in marketing their Payroll Service products is by using the Marketing Mix 7P (Product, Price, Place, Promotion, People, Process, Physical Evidance), and the concepts applied in its marketing in the form of needs, wants, demands, products, value, costs, satisfaction, exchange and markets. And the type of payroll system used is BNIDirect which is one of a number of financial management service provided by BNI Syariah KCP Jababeka-Cikarang.